Health and Liver Diagnostic Markers Influencing Glycemia in Subjects with Prediabetes: Preview Study - Gareth Stratton (Diagnostics, 2024)
Introduction: Glucose homeostasis may be dependent on liver conditions and influence health-related markers and quality of life (QoL) objective measurements. This study aimed to analyze the interactions of glycemia with liver and health status in a prediabetic population. Subjects and methods: This study included 2220 overweight/obese prediabetics from the multinational PREVIEW project. Anthropometrics; clinical, metabolic and other health-related markers; and QoL variables were analyzed. Univariate and multilinear-adjusted regression models were run to explain the interrelationships and effect modification between glycemia, health-related QoL (applying SF-12) and metabolic/liver health (using the HSI, a putative marker of fatty liver). Results: Relevant age/sex interactions were found concerning the levels of insulin, HOMA-IR, C peptide and transaminases in this prediabetic population. Multivariate models identified age, sex, glucose, WC and QoL as important predictors of HSI variability (adj. R value = 0.1393, p < 0.001), whereas the QoL status was statistically related to age, sex, HOMA-IR and HSI (adj. R value = 0.1130, p < 0.001) in this glycemia-impaired group. Furthermore, the QoL values declined with increased HSI scores, where a significant interaction was found (p = 0.011) when the data were analyzed when comparing lower glycemia vs. higher glycemia in prediabetics. Indeed, an effect modification was featured depending on the glycemia levels concerning the QoL and HSI worsening. Conclusion: Glycemia associations with the QoL status and liver metabolism markers were evidenced, with clinical implications for diabetes and liver disease precision management given the modification of the QoL outcomes depending on the liver status and glycemia concentrations. Notably, independent associations of circulating glucose with age, sex, adiposity, inflammation and C peptide levels were found.